Cellulase activity of Bacillus velezensis isolated from soil in a dairy farm - P Narkthewan; W Makkapan (My University, 2019)
Abstract The aim of the present study was to isolate and screen cellulase producing bacteria from soils including characterizing the cellulase activity of the identified bacterial strain. Screening of the cellulase producing bacteria was performed on a carboxymethylcellulose (CMC) agar (pH 7.0) plate at 37°C for 3 days. Bacterial isolate, namely CC1-1, showed the highest cellulase activity on the CMC agar plate. Subsequently, it was identified as Bacillus velezensis based on 16S rDNA gene sequence analysis. Cellulase production was carried out under submerged fermentation. The maximum CMCase and FPase activity of 0.030 U/ml and 0.047 U/ml were obtained after 20 h and 32 h, respectively. The optimal pH and temperature of CMCase activity were 6.0 and 60°C, respectively. The cellulase activities were active in a broad pH and temperature range. The CMCase activity was stable at pH 6.0-7.0, 37°C for 120 min and the stability of CMCase was revealed at 50-60°C for 90 min with over 80% remaining activity. However, the optimum pH and temperature of FPase activity were 7.0 and 50°C, respectively. The FPase activity was stable at pH 6.0, 37°C for 90 min and its activity was stable at 60°C for 60 min with over 80% remaining activity. Due to its particular properties, cellulase-producing B. velezensis could be a potential candidate for the composting process.
Keywords: Biofuel production and bioconversion